Terapevtski postopki v obravnavi starejših s težavami v duševnem zdravju - Starovasnik Žagavec, Barbara (Medicinski razgledi, 2011)
This paper presents areview of the most documented currently used psychotherapeutic methods in clinical work with the elderly. Psychological interventions in the elderly are used in addition to psychotropic drugs or as a substitute for the use of drugs when the elderly reject them or when drugs cause potentially harmful side effects. Cognitive-behavioral therapy has been empirically tested and validated as the most effective form of psychotherapeutic tre atment. It is therefore the method oftreatment most of ten used. Hence, cognitive-behavioral therapy has been adopted as the dinical standard of supportive therapy to psychotropic drugs in the treatment of the elderly, and in cases involving emotional adaptation to physical illness, cognitive-behavioral therapy may be us ed as the only form of therapy. Interpersonal and/or systemic therapeutic approaches are used when changes in relationships and/or individual rules within a family or in the broader socialenvironment are needed. In addition, generic approaches can be individually adapted according to the problems presented by older patients. Generic approaches are especially ap pro pri ate for use in institutions, since these are primarily airned at improving the therapeutic milieu, as well as the patient's overall well-being and quality of life. Irrespective of the therapeutic approach used, one should be aware that successful work with the elderly requires mutual respect, understanding of their experiences and providing a psychosocial environment that fosters their well-being. Due to theincreasing number of the elderly in our society, effective therapeutic approaches are becoming not only desirable, but essential.
Keywords: Geriatric Psychiatry; Spoznavno zdravljenje; Patient-Centered Care; Geriatrična psihiatrija; K bolniku usmerjena oskrba; Psychotherapy; Cognitive Therapy; Psihoterapija; Starostniki; Aged